Testing the Packer Theorem: The Efficiency of Florida’s Criminal Circuit Courts - Ferrandino, Joseph (American journal of criminal justice, 2014)
Herbert Packer’s models of the criminal process are criminal justice theorems, often the foundation of student introduction to the field in introductory textbooks. To date, there is little empirical analysis of the conceptual foundations of the process-based models, namely that courts are more efficient through the utilization of plea bargains, while an increase in trials necessarily decreases efficiency. The present results reveal wide variability in Florida circuit criminal court efficiency within and between circuits from 2004/05 to 2010/11. Regression analysis revealed that the year over year difference in both plea bargain (β = .14) and trial percentage (β = .13) significantly predicted ( p < .05) year over year changes in efficiency, but explained a small amount of the variance ( R ^2 = .026) controlling for other factors (total model R ^2 = .58–.62). These results show there is more capacity for trials within the Florida courts, and an increase in trials does not negatively impact court efficiency as expected but that other factors are far more relevant in explaining changes in efficiency outcomes. Furthermore, the Packer “assembly line” analogy, a basic tenet of the criminal process, is not found: plea bargains do not strongly predict or explain court efficiency, with structures playing a greater role in court outcomes than the processes conceptualized by Packer. The application to courts and impact on criminal justice education are discussed.